FORMING A PERSONALITY OF RELIGIOUS MODERATION IN A MULTICULTURAL SCHOOL BASED ON LIVING VALUES EDUCATION - Al Faruq, Umar; Arifa, Zakiyah; Taman, Mona (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study seeks to reveal in-depth the process of character forming of religious moderation in a multicultural school, Selamat Pagi Indonesia High School, in the city of Batu, East Java, Indonesia. This research used an experimental method with the type of case study research. Data were obtained through field observations, in-depth interviews, and document studies. The results showed that the process of character education for religious moderation in Selamat Pagi Indonesia High School was implemented from the beginning of students' learning in that school. They continued until they finished the learning process in that school. The process of character education of religious moderation was carried out by inculcating the doctrine of religious moderation values that are consistent with the values contained in living values education (LVE). In addition, the process of character education for religious moderation was implemented by providing direct experience and familiarization for all students in various activities reflecting religious moderation in both the school and the residential environment. Moreover, the character education process for religious moderation has also been implemented in the form of good examples from teachers and supervisors in the school and student dormitory.